The People of Jamaica - Reynir Grétarsson 1972- (2013)
The People of Jamaica are in many ways different from the people where I come from, Iceland. Even if the people in Jamaica are generally warm and friendly, there exist huge inequality as well as other problematic social issues that are alien in Iceland. Class division, violence, poverty. Writers are often quick to cite history as the cause for those problems. They blame colonisation and, most of all, slavery. The claim is that slavery had such an enormous social effects that those effects reverberated through history, still to be felt in the present. Society that was built and maintained by violence was bound to remain violent and not easily change. Attitudes towards race, role of the sexes, and the right to the spoils are still shaped by this past. This applies to practically any aspect of society, including arts. Going through the history and matching the social challenges in contemporary Jamaica with respective challenges in the past, one is easily persuaded: the problems have its roots or at least contributing cause in the distant past of the darkest times in human history.